Spatially Continuous Interpolation of Water Stage and Water Depths Using the Everglades Depth Estimation Network (EDEN) - Leonard Pearlstine; Aaron Higer; Monica Palaseanu; Ikuko Fujisaki; Frank Mazzotti (EDIS, 2007)
Circular 1521, a 34-page report by Leonard Pearlstine, Aaron Higer, Monica Palaseanu, Ikuko Fujisaki, and Frank Mazzotti, documents the procedures used in generation of EDEN water stage and water depth interpolated surfaces. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, July 2007. Minor revision September 2007.